Pengaruh Kepemilikan Manajerial, Karakteristik Eksekutif, Dan Capital Intensity Terhadap Tax Avoidance Pada Perusahaan LQ 45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Minda Muliana Br. Sebayang; Rahma Isnaini Rangkuti; Devi Ayu Putri Sirait (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2024)
Testing the effect of capital intensity, executive characteristics, and management ownership on tax avoidance in LQ 45 companies listed on the Indonesia Stock Exchange in 2018 to 2022. In this study, capital intensity, executive characteristics, management ownership, and tax avoidance are independent factors, while tax avoidance is the dependent variable. The study population consisted of 45 LQ 45 companies or entities listed on the Indonesia Stock Exchange between 2018 and 2022. The sampling strategy used purposive sampling as the method of choice, and the number of samples was 23 companies that met the research criteria. The research findings indicate that managerial ownership of 45 LQ businesses scheduled to be listed on the Indonesia Stock Exchange between 2018 and 2022 will significantly and adversely affect tax avoidance. The impact of executive quality on tax avoidance is not statistically significant or detrimental. The relationship between capital intensity and tax avoidance is significant and positive retention. Between 2018 and 2022, management ownership, executive characteristics, and capital intensity have a good and large influence on tax avoidance in LQ 45 companies listed on the Indonesia Stock Exchange.